2006
DOI: 10.1002/cbdv.200690031
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability of Dehydrophenylalanine‐Containing Model Peptides as Probed by Infrared Spectroscopy: a Case Study of an α‐Helical and a 310‐Helical Peptide

Abstract: The temperature-dependent secondary-structural changes in the two known helical model peptides Boc-Val-deltaPhe-Ala-Leu-Gly-OMe (1; alpha-helical) and Boc-Leu-Phe-Ala-deltaPhe-Leu-OMe (2; 3(10)-helical), which both comprise a single dehydrophenylalanine (deltaPhe) residue, were investigated by means of FT-IR spectroscopy (peptide film on KBr). Both the first-order and the better-resolved second-order derivative IR spectra of 1 and 2 were analyzed. The nu(NH) (3240-3340 cm(-1)), the Amide-I (1600-1700 cm(-1)), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…In addition, ligands with the phenyl ring in the Z configuration show distinctly higher ability of metal ion binding through nitrogen atoms, when compared to peptides with Δ (E) Phe. , The deprotonated carboxylic group also participates in coordination of the metal ions, but this interaction is much weaker for the Z isomer of ΔPhe than the E counterpart due to the steric hindrance. This effect was observed to be stronger for short peptides. , Recently, several experimental and theoretical studies on molecular structure of dehydropeptides have been reported, but they have been focused mainly on the analysis of IR, , circular dichroism, NMR spectra, and X-ray diffraction supported by quantum-chemical calculations. , Up to now, the Raman and SERS profiles of short peptides containing dehydroamino acid residues have been studied by our group only. , In our previous work we reported IR, Raman, and SERS spectra of three dipeptides Boc-Gly-X, where X is ΔAla, Δ (Z) Phe, and Δ (E) Phe. SERS spectra were collected by using Ag sol as a metal substrate.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…In addition, ligands with the phenyl ring in the Z configuration show distinctly higher ability of metal ion binding through nitrogen atoms, when compared to peptides with Δ (E) Phe. , The deprotonated carboxylic group also participates in coordination of the metal ions, but this interaction is much weaker for the Z isomer of ΔPhe than the E counterpart due to the steric hindrance. This effect was observed to be stronger for short peptides. , Recently, several experimental and theoretical studies on molecular structure of dehydropeptides have been reported, but they have been focused mainly on the analysis of IR, , circular dichroism, NMR spectra, and X-ray diffraction supported by quantum-chemical calculations. , Up to now, the Raman and SERS profiles of short peptides containing dehydroamino acid residues have been studied by our group only. , In our previous work we reported IR, Raman, and SERS spectra of three dipeptides Boc-Gly-X, where X is ΔAla, Δ (Z) Phe, and Δ (E) Phe. SERS spectra were collected by using Ag sol as a metal substrate.…”
Section: Introductionmentioning
confidence: 88%
“…Additionally, the ΔPhe moiety exists in the two isomeric forms, Z and E, which can influence the biological activity of the peptide. 8 This class of nonproteinogenic amino acids can be found in many biological peptides with antiviral, antitumor, anti-inflammatory, or immunosuppressive activities. 9,10 Dehydroamino acids are also used in de novo synthesis of protein mimics for structure−function relationship studies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Spectroscopic measurements were extensively employed for the assessment of the local (NMR) and overall (IR absorption) conformational properties of ΔPhe‐rich peptides in solution; although with these compounds, CD spectroscopy (refer to later in the text) proved by far to be the technique of choice. In particular, IR absorption studies were not only conducted in solvents of low polarity but also extended to the solid state (KBr film, ZnSe crystal surface, Ag nanocolloids, and electrodes) as well, where related spectroscopies (Raman, surface‐enhanced Raman scattering, and vibrational CD) were also utilized . These analyses were expanded to N α ‐methylated ΔPhe residues where the cis tertiary amide conformation was shown to prevail.…”
Section: Cαβ‐didehydro‐α‐amino Acid‐containing Peptidesmentioning
confidence: 99%